Clinical Efficacy of Fresh Amniotic Membrane Transplantation in Non- Healing Corneal Ulcer - Reny Setyowati; Kristian Goenawan; Suhardjo Prawiroranu (Majalah Oftalmologi Indonesia, 2019)
Objective: Severe corneal ulcer requires immediate intensive topical antibiotics, although potentially toxic to corneal epithelium and may contribute for prolonged corneal epithelial defect. Fresh-amniotic membrane transplantation (F-AMT) could act as an adjuvant therapy that counterbalances the epithelial toxicity effect and exerting antimicrobial actions. This study evaluates the clinical improvement and factors associated with the success rate of F-AMT using suturing technique. Methods: This was a retrospective cohort study of 28 patients (28 eyes) conducted at Dr Sardjito General Hospital, Yogyakarta. Inclusion criteria were patients with severe corneal ulcer unresponsive to conventional medical treatment who underwent multilayer F-AMT using suturing technique. Clinical improvement such as hypopyon, size of the corneal defect, and antibiotic medication were evaluated. Results: Corneal epithelial healing was effectively restored at 25 days post F-AMT. There were statistically significant difference in patient’s blepharospasm (p= 0,00) and pain scale postoperative (p=0,00). There was no significant difference in patients visual acuity postoperative. Factors such as the size of the corneal defect, hypopyon, leucocyte count and neutrophil count were not correlated to epithelial healing. Failure was noted in 7 patients (25%) because of a persistent corneal defect. No patient developed major immediate postoperative complications. Conclusion: F-AMT could be an optional adjuvant therapy with excellent results to treat non-healing severe corneal ulcer unresponsive to medical treatment by promoting epithelial healing.